Artificial Sinks: Opportunities and Challenges for Managing Offsite Nitrogen Losses. (August 2013) - Gold, Arthur J.; Addy, Kelly; David, Mark B.; Schipper, Louis A.; Needelman, Brian A.
Abstract Advanced control measures are needed after nitrogen (N) leaves agricultural fields and begins to flow through a catchment. Bioreactors – simple, wood‐chip filled trenches – and constructed wetlands afford additional treatment to reduce N from agricultural lands, but their success requires informed adoption and placement. Rates of N removal in field studies of bioreactors vary based on carbon substrate, hydrologic setting, temperature, N loading and hydraulic residence time. From limited measures in constructed wetlands, N removal can be substantial and influenced by seasonality. Additional research is needed to understand uncertainty and variability associated with these systems. Further synthesis of data from research and demonstration sites combined with geospatial tools will help guide the design and siting of these systems at regional and local scales. Professional and student training and web‐based data information exchange will advance the adoption and strategic placement of appropriate bioreactor and constructed wetland designs to remove edge‐of‐field N contributions.